Peran Layanan TANYA BPMP dalam Transformasi Digital Pelayanan Pendidikan - Rabiyatul Adawiyah; Triwid Syafarotun Najah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the role of the TANYA BPMP service in supporting digital transformation at the Integrated Service Unit (ULT) of the Education Quality Assurance Agency (BPMP) in Central Kalimantan Province. The research method used is a qualitative descriptive approach through observation, interviews, and document studies related to the implementation of the website-based service directly integrated with the Zoom application. The results show that the TANYA BPMP service plays an important role as an interactive communication medium that accelerates service processes, improves digital literacy in the community, and expands access to educational services even in remote areas. Furthermore, this service promotes bureaucratic efficiency, transparency, and accountability through integrated digital documentation. However, limitations in internet connectivity and digital competence of staff remain major obstacles to optimizing service implementation. Overall, TANYA BPMP represents a concrete example of an innovative and adaptive digital transformation of public services in the regional education sector.